Preliminary Study on the Expression of Toll-Like Receptors 7 and 8 in Bladder Urothelial Tumors. Issue 4 (October 2015) - Garau, Gianmarco; Rocca, Paolo Cossu; Manca, Alessandra; Madonia, Massimo; Siracusa, Giuseppe; Sotgiu, Giovanni; Corbu, Carlo
The aim of the study was to demonstrate the expression of Toll-like receptor (TLR)-8 and to confirm the expression of TLR-7 on bladder transitional cell carcinomas (TCCs) analyzing the changes in expression between low-grade (LG) and high-grade (HG) and between non-muscle invasive (NMIBC) and muscle-invasive (MIBC) bladder cancers. In our study, 25 patients who underwent transurethral resection (TURB) for bladder TCC have been selected. Thirteen of those had an LG form, while the other cases were classified as HG; the lesions were NMIBC in 18 patients and MIBC in the others seven. The analysis of TLRs expression has been performed by immuno histochemistry. TRL-8 expression seems to be higher in MIBC (85%) than in NMIBC (78%), but it is associated with a reduced percentage of immuno reactive cells and with a lower intensity. The expression had a large nuclear localization in NMIBC (80%), althoughit was mainly cytoplasmic in MIBC (72%). TLR-7 was expressed in all NMIBC samples (where the localization was mainly nucleo-cytoplasmic) and in the 71% of MIBC samples (mainly in the nucleus). A higher expression of TRL-8 in HG TCC had been observed, while TRL-7 seems to be more expressed in LG forms. Our study allowed to document the immunohistochemical expression of TLR-8 in TCCs, confirm the immunohistochemical expression of TLR-7, and suggest an increased expression of TLR-7 in LG TCC and NMIBC, and a prevalent expression of TLR-8 in HG TCC and MIBC.